School reintegration after a burn injury : a qualitative study exploring the psychosocial difficulties experienced by a group of paediatric burn survivors during the school reintegration process - Baumann, Elsje (Department of Psychology, 2014)
Sustaining a burn injury is one of the most traumatic accidents a child or adolescent can experience. In South Africa paediatric burn injury is a significant social problem and incident rates tend to be elevated in informal settlements because of the reliance on fossil fuels (paraffin, wood, and coal) for heating and cooking. The role of mental health professionals in helping young burn survivors and their families through their traumatic ordeal is of paramount importance. There is currently a shortage of specialised psychosocial assistance for burn patients and their families in South Africa. Given the enormous challenge of paediatric burn injury in South Africa it is alarming that so little research has been undertaken in the field. The present knowledge regarding this issue is largely reliant on international research, which cannot always be generalised to the specific challenges posed by the South African context. The purpose of this study was to provide local insight into the psychosocial adjustment of burn survivors that can inform intervention programmes in this field. In order to explore the psychosocial adjustment of paediatric burn survivors during the school reintegration process it was decided to interview the burn survivors, their parents and their school teachers. The sample comprised 7 paediatric burn survivors and their respective caregivers and teachers. The study was conducted using a qualitative paradigm. Data was collected by conducting semi-structured interviews with the participants and their caregivers and teachers. Data was analysed by conducting a thematic analysis of the transcribed narratives of the participants, their caregivers and teachers. The study yielded important information about the social contexts of a small group of burn survivors and their families and the challenges that they face during the school re-integration process and psychosocial adjustment in generaL The majority of the families in this study were experiencing extreme socio-economic difficulties. This was a strong contributing factor in their limitations to fulfil their roles in supporting the burn survivor. The mental health difficulties of parents as well as participants before and after the burn injury showed that the burn injury often meant an additional stress factor to already existing problems. It was found that the burn injury also poses an additional challenge to most of the interviewed teachers, who have to cope with multiple challenges in their classes and therefore have very limited resources (time, empathy, attention) to attend to the specific challenges of the re-integration of burn survivors. The different layers of problems that were experienced by participants, their families and teachers highlighted the reality of the South African context.